PENINGKATAN KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA MELALUI KELOMPOK BELAJAR BERDASAR SOSIOMETRI - Nurdiansyah, Erwin (Indonesian Journal of Educational Studies, 2018)
This research is a classroom action research (classroom action research). This study uses instruments of observation sheets, cycle tests, and documentation. The data obtained were analyzed using qualitative and quantitative data analysis techniques, namely: reducing data, presenting data, drawing conclusions and verification. The ability to solve students' math story problems in cycle I is an average of 66.56, students who complete learning are 21 students or around 65.63% and those who have not completed learning are 11 students or about 33.38%. Whereas in cycle II that is an average of 76.09, students who complete learning as many as 23 people or about 71.88% of people and those who have not completed 10 people or about 31.25%.